Digital Forensic Analysis to Improve User Privacy on Android - Kim, Hyungchan; Shin, Yeonghun; Kim, Sungbum; Jo, Wooyeon; Kim, Minju; Shon, Taeshik (Sensors, 2022)
The Android platform accounts for 85% of the global smartphone operating-system market share, and recently, it has also been installed on Internet-of-Things (IoT) devices such as wearable devices and vehicles. These Android-based devices store various personal information such as user IDs, addresses, and payment information and device usage data when providing convenient functions to users. Insufficient security for the management and deletion of data stored in the device can lead to various cyber security threats such as personal information leakage and identity theft. Therefore, research on the protection of personal information stored in the device is very important. However, there is a limitation that the current research for protection of personal information on the existing Android platform was only conducted on Android platform 6 or lower. In this paper, we analyze the deleted data remaining on the device and the possibility of recovery to improve user privacy for smartphones using Android platforms 9 and 10. The deleted data analysis is performed based on three data deletion scenarios: data deletion using the app’s own function, data deletion using the system app’s data and cache deletion function, and uninstallation of installed apps. It demonstrates the potential user privacy problems that can occur when using Android platforms 9 and 10 due to the leakage of recovered data. It also highlights the need for improving the security of personal user information by erasing the traces of deleted data that remain in the journal area and directory entry area of the filesystem used in Android platforms 9 and 10.
Keywords: Android filesystem; Android forensics; Android platforms; Ext4 filesystem; Filesystem; Permanent deletion; Personal information; Smart phones; User privacy; Computer Security; Mobile Applications; Privacy; Smartphone; Wearable Electronic Devices; Android filesystem; Android forensic; digital forensic; Ext4 filesystem; permanent deletion; user privacy